PERBANDINGAN SUMBER-SUMBER HUKUM DAN KARAKTERISTIKNYA DALAM KAJIAN SYARIAH DAN PERUNDANG-UNDANGAN - Ja'far Shodiq ‎ ‎ ‎ (Syakhsiyah Jurnal Hukum Keluarga Islam, 2022)
The presence of pawnshops in Indonesia is no stranger. This institution has become very popular among the people when Eid arrives. It is a tradition for travelers to pawn their valuables before the month of Shawwal. Seen from the point of view of its function as a source of law in a formal sense, every agreement, whether it is called a law-making treaty or a treaty contract, is law-making, meaning it gives rise to law. It can be added that generally, law-making treaties are multilateral agreements, while special agreements are bilateral agreements. pawn according to the Civil Code (Burgenlijk Wetbiek) Book II Chapter XX article 1150, is: a right that is obtained by a person who is indebted to a movable object, which is handed over to him by a debtor or another person on his behalf and who gives power to the creditor it is to take payment of the item in priority over other creditors, except the costs for auctioning the item and the costs incurred to save it after the item is mortgaged, which costs must take precedence. This research was created so that the public knows about the sources of law and characteristics in the study of Sharia and legislation.